RESULTS OF THE INTRODUCTION OF CLINICAL PATH TO SURGERY FOR BREAST CANCER - YUGUCHI, Taku; Oomori, Toshihiro; ARUGA, Hiroko; CHISUWA, Hisanao; KOIKE, Hideo; TAUCHI, Katsunori (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2003)
In order to standardize the medical treatment, increase the efficiency of service, improve the medical quality, and shorten the hospital stay, we have introduced the clinical path to all the departments in this hospital. This paper deals with the results of the introduction. Subjects were 14 cases of breast cancer treated from April 2000 to March 2001 before the introduction and 25 cases of breast cancer from April 2001 to March 2002 after the introduction. With thoroughgoing standardization of medical treatments, conventional treatments without any particular purpose were eliminated and resultantly early getting away from bed rest and early discharge became possible. Path table was made from ordering system by standardizing the admission order by diseases, and all necessary medical performances were surely done. All the patients were explained about precise therapies and their courses after admission by using the path table to substantiate the informed consent. After the introduction of the clinical path, the mean hospital stay was shortened and total medical expenses decreased, but the medical expenses par day increased. Moreover, the using rate of beds temporarily decreased, but the rotation rate of beds and number of operations under general anesthesia increased. We think that the introduction of clinical path is valuable in terms of the severe trend of medical world.